Du couvent au collège : relations, circulations et conflits entre San Pablo et San Gregorio à Valladolid - Diana Olivares Martínez (Mélanges de la Casa de Velázquez, 2022)
This paper aims to explore the relationship between two important Dominican institutions settled in Valladolid. Both were key to the impulse and consolidation of the reformation of the Order in Castile at the end of the 15th Century. The foundation of the College of San Gregorio in 1487 by Alonso de Burgos, Dominican friar and bishop of Palencia, in a land given by the adjacent convent of San Pablo started these torturous relations. However, the wish of the prelate, according to what is written in the College statutes, was to guarantee a life in harmony between the two communities. The paper analyses how the layout of the College was designed with in mind the transit of the friars from the convent to the college, in order to attend the university courses, and vice-versa.